Actualization Of Islamic Religious Education In Character Formation - Fawaiz, Rohmatul (Annpublisher, 2025)
Background. Allah SWT created humans as a caliph on earth. Allah SWT created humans with the main task of worship, as stated in the Qur'an. وما خلقت الجن والا نسى الا ليعبدون